Diseño e implementación de un radar de banda estrecha, utilizando SDR para la detección de objetos y medición de distancia. - Pino Enríquez, Jeffersson Pascal (2023)
The aim of this research project is to design and implement a narrowband radar using Software Defined Radio (SDR) for object detection and distance measurement. The design was developed on the open-source software platform, GNURadio, and implemented on two active learning modules of Software Defined Radio, called "Adalm Pluto". The system is based on the Multiple Frequency Continuous Wave (MFCW) radar algorithm and consists of two continuous wave transmitters and two calibrated receivers operating at different frequencies with a separation of Δf, which determines the maximum range of measurement, . It is possible to determine the distance of a detected object thanks to the phase shift of the signal when it is reflected off an object at a distance R and returns to the radar with a phase shift on each carrier. The transmission signals are eliminated after being received, obtaining only the phase shift module (ΔΦ). Therefore, we have a maximum distance without ambiguity when ΔΦ=2π, the chapter one provides background information, motivation, problem statement, and project justification, the chapter two discusses the theoretical and physical foundation of the radar system, the chapter three outlines the research methodology, variables, necessary tools, and carries out the design, implementation, and testing of the radar, the chapter four presents the results and their analysis using statistical and estimation tools such as relative error analysis, mean comparison, confidence intervals, and quality control of the measurements taken by the prototype. Finally, the chapter five provides the conclusions and recommendations of the research